Sesja plenarna IVCongenital melanocytic naevi - Włodarkiewicz, Adam; Sobjanek, Michał; Michajłowski, Igor (Dermatology Review/Przegląd Dermatologiczny, 2009)
Congenital pigmented naevi are benign proliferations of melanocytes occurring relatively frequently. They comprise morphologically various skin lesions and may transform into or be a sign of serious clinical events. The most important is that melanoma can develop in them. They can be an indicator of neurocutaneous melanosis or they can coexist with other malformations such as spinal cord anchoring syndrome. Congenital pigmented naevi are generally not accepted from a cosmetic point of view and cause serious psycho-social problems due additionally to consequences of numerous surgical interventions